2016
DOI: 10.3389/fpsyg.2016.01787
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Resilience Scale (ARS-30): A New Multidimensional Construct Measure

Abstract: Resilience is a psychological construct observed in some individuals that accounts for success despite adversity. Resilience reflects the ability to bounce back, to beat the odds and is considered an asset in human characteristic terms. Academic resilience contextualizes the resilience construct and reflects an increased likelihood of educational success despite adversity. The paper provides an account of the development of a new multidimensional construct measure of academic resilience. The 30 item Academic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
300
0
101

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(413 citation statements)
references
References 41 publications
12
300
0
101
Order By: Relevance
“…Liebenburg, Ungar, and Van der Vijver (2012) used a sample of two groups of youths in Canada, and demonstrated that the CHKS is reliable and valid in assessing resilience among Available Online at: https://grdspublishing.org/ youth from various cultural backgrounds. In a related study on the psychometric properties of the CHKS, Cassidy (2016) in a study involving a sample of undergraduate students (N D 532) established that the scale has good internal reliability and construct validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liebenburg, Ungar, and Van der Vijver (2012) used a sample of two groups of youths in Canada, and demonstrated that the CHKS is reliable and valid in assessing resilience among Available Online at: https://grdspublishing.org/ youth from various cultural backgrounds. In a related study on the psychometric properties of the CHKS, Cassidy (2016) in a study involving a sample of undergraduate students (N D 532) established that the scale has good internal reliability and construct validity.…”
Section: Methodsmentioning
confidence: 99%
“…The strengths-based approach to resilience emphasizes certain individual behaviors, attitudes, and competencies as common components of resilience. Notably, most of these components are mainly developed in school (Knight, 2007;Cassidy, 2016). Researchers are paying more attention to how school type affects students' academic resilience.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to investigate the psychometric properties of the Academic Resilience Scale (Cassidy, 2016). Based on the results, this scale is an valid and reliable tool for measuring academic resilience and can be used as a valid and reliable tool for Iranian students.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to construct validity, its criterion validity has been reported by calculating the correlation coefficient with the General Academic Self-Efficacy Scale (Cassidy & Eachus, 2002), 0.49. The Cronbach's alpha of the scale was 0.90 (Cassidy, 2016). Academic Self-Regulation Scale (Sevari & Arabzade, 2013): The Academic Self-Regulation Scale was developed by Sevari & Arabzade (2013) to measure the variable of academic self-regulation.…”
Section: Research Tools Academic Resilience Scale (Cassidy 2016)mentioning
confidence: 99%
See 1 more Smart Citation